Z problematyki lucrum cessans w obrocie uspołecznionym - Napierała, Jacek (Wydział Prawa i Administracji UAM, 1983)
Failing a legal or contractual provision - to the contrary, redress of damages covers the losses borne by the injured person as well as the profit he could have made if he had not sustaineld the damage. Dogmatic amid legal probletms emeriging by delimiting a scope of that form of a profit loss which is loss of returns expected by the injured unit of economy is the subject of this study. The analysis has to be opened with stating the relation of that element of damage concept to its other types described in legal acts as "direct damage", "indirect damage", "actual damage", "future damage", "damage in the amount of usual commercial value of goods", or "expected damage". These terms can be usually observed when discussing departures from the principle of full damages. Assessing value of lost profits has to account for an individual situation of a specific injured person. There is no justification on the grounds of Polish law to emiploy a concept of the so-called "abstract profit". This fact however does not exclude a possibility of invoking certain typical standard situations when assessing value of lost profits, yet an actual and specific character of damage calculation is not upset. There is a problem to be solved on reconstruction of a hypothetical course of events which could have effected possible profits: can the scope of debtor's liability be influenced by the fact that a loss of profits would have ocurred even if the event producing damage had not happened? Another problem requires an answer to the question whether the injured unit should recover damages reduced by profits it could have gained undertaking other type of activities? Still other questions can emerge when assessing what part of the expected (planned) financial gain can be considered to be lost within the meaning of art. 316)1 § 12 of the civil code. It is a fragment of a wider problem i.e. the effect of financial law institutions on the application of civil law provisions. The author has also made an effort to prove that a postuliate raised in literature as to necessity of proving that a loss of profits was "actually" borne does not contradict the fact that a hypothetical situation of the injured can only be assessed at most, with a high degree of probability. Employing a traditional division to lucrum cessans and damnum emergens by the Polish legislator even in economic relations can prove the advisability of using — to a proper degree — solutions elaborated by practice and doctrine of civil law when discussing problems characteristic for law on socialized transactions. Legislative solutions as well as views of the doctrine of law on economic activities of the socialist States were presented in its essentials.
On lucrum cessans problems in socialized transactions